Application of the Information-Motivation-Behavioral Skills Model to Tertiary Preventive Behavior in Osteoarthritis - Nisrina Nafisa; Setyo Sri Rahardjo; Bhisma Murti; Hanung Prasetya; Sumardiyono; Revi Gama Hatta Novika (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: Osteoarthritis (OA) is a type of degenerative disease in which chronic joint inflammation occurs that can occur in the elderly. People with osteoarthritis will feel pain and experience functional limitations. Physiotherapy helps prevent and minimize further joint damage. The success of the rehabilitation program depends on the patient's skills in doing exercises, lifestyle changes, such as maintaining weight and avoiding activities that improve the joints. This study aims to analyze the influence of the Application of the Information Motivation Behavioral Skills Model (IMB) on the tertiary preventive behavior in osteoarthritis patients. Subjects and Method: This was a cross sectional study conducted at a physiotherapy clinic in Surakarta, in January 2025. A sample of 210 osteoarthritis patients was selected using the fixed diseases sampling. The dependent variable was the tertiary preventive behavior. Independent variables were information, motivation, and behavioral skill. The data were collected using questionnaire and analyzed using a path analysis. Results: Tertiary preventive behaviors in OA patients increased with behavioral skills (b= 0.45; 95% CI= 0.34 to 0.55; p<0.001) and motivation (b= 0.44; 95% CI= 0.34 to 0.53; p<0.001). Behavioral skill increased with information (b= 0.47; 95% CI= 0.37 to 0.57; p<0.001) and motivation (b= 0.35; 95% CI= 0.25 to 0.46; p<0.001). The goodness of fit indices were p= 0.285; RMSEA= 0.026 (<0.050); CFI= 1.0 (≥0.90); TLI= 0.99 (≥0.90); and SRMR= 0.01 (<0.050). Conclusion: Tertiary preventive behaviors in OA patients increases with behavioral skill and motivation. Behavioral skill increases with information and motivation.